Infrared thermography for detecting defects in concrete structures - Sirca Jr., Gene F.; Adeli, Hojjat (Journal of Civil Engineering and Management, 2018)
The traditional methods for inspecting large concrete structures such as dams and cooling towers require erecting large amounts of scaffolding to access the surface of the concrete structure in order to sound the concrete with an impact device or hammer to expose the damaged or defective areas.  Another method for accessing the surface of a large concrete structure is to employ climbing inspections which poses a considerable safety risk. These traditional methods are used to determine defect or damage within a few inches of the surface. In addition to the logistic difficulty of these methods a hammer can cause damage if care is not taken. Further, it can cover only a small area. Infrared Thermography (IRT), also referred to as thermal imaging, utilizes the infrared spectrum to show differences in heat dissipating from a structure using a thermal imaging camera. This paper presents a review of the IRT research for detecting defects in concrete structures. Health monitoring and damage detection of large structures such as bridges and high-rise buildings has been a very active area of research in recent years. The two main approaches explored by researchers are vibration-based health monitoring and camera-based vision technology. IRT remains to be another promising technology for economical health monitoring of structures.